Optimizing Branding Strategies Through Event Booths to Improve Sales at PT The Agung Pamungkas - Akhmad Alief Rachmaddhany; Muhammad Ahmi Husein (Community Development and Empowerment, 2026)
The development of the electric vehicle industry in Indonesia has experienced quite rapid growth along with increasing public awareness of the use of environmentally friendly transportation. This condition encourages electric motorcycle sales companies to implement effective marketing and branding strategies to be competitive in the market. One strategy that can be implemented is the use of event booths as a promotional medium and direct interaction with consumers. This article aims to analyze the optimization of branding strategies through the implementation of event booths in increasing electric motorcycle sales at PT The Agung Pamungkas. The research method used is a descriptive method with a qualitative approach through observation and direct involvement of the author in marketing activities, promotional content creation, and interaction with consumers during the event. The results show that event booths are able to increase brand awareness, strengthen the company's image, and increase consumer purchasing interest in electric motorcycles. In addition, attractive booth designs, communicative services, the use of digital media, and the provision of promotions during the event also influence the company's sales increase.